How is Justice Represented in the Process of Selecting Executives of Education? Giving a "Voice" to the Participating Teachers - Πολυμεροπούλου Βασιλική (Education Sciences, 2022)
This study attempts to give voice to the participants in the process of selecting schools’ principals during the 2017 crises in order to express their opinion on their fair treatment by the members of the competent selection board during the oral interview. Focus given on a particular secondary education directorate. An electronic questionnaire was given to the participating candidates for data collection which was answered by 61 of the 96 participants in the process. The data analysis methodology includes quantitative analyzes of descriptive but mainly inductive statistics. Adams's theory of justice was used to interpret the data. It appeared that the majority of the participants considered that they were treated fairly by the competent selection board during the oral interview but in the case of their fellow candidates the selection board acted in a discriminatory manner in terms of ratings. This attitude of the selection board was due to the previous personal relationship of the candidates with the members of the selection council and to the party involvement. Proposals at the level of educational policy are proposed.